Prophetic Education dalam Hadis Nabi SAW: Integrasi Ilmu, Iman, dan Akhlak dalam Tujuan Pendidikan Islam Kontemporer - Hadiyanto; Gangan Sayid Mikdad; Ripan Maulana; Ghifar Ramadhan; Maslani (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study explores the concept of Prophetic Education in the hadiths of the Prophet Muhammad ﷺ as an integrative paradigm that unites knowledge (‘ilm), faith (īmān), and morality (akhlāq) within the aims of contemporary Islamic education. In Islam, education is not merely an intellectual process but also a means of spiritual purification (tazkiyah al-nafs) and moral formation (ta’dīb), as emphasized in the Prophet’s saying: “Seeking knowledge is an obligation upon every Muslim” (Ibn Mājah, no. 224). Using a qualitative-descriptive approach with thematic (maudhu‘i) analysis, this study examines educational hadiths found in the Kutub al-Sittah and supports them with secondary literature from scholars such as al-Attas (1980), Kuntowijoyo (1991), and al-Ghazālī (2000). The analysis employs a contextual hermeneutic method to interpret the normative and spiritual meanings of the hadiths in light of modern educational challenges. The findings reveal that Prophetic Education encompasses three core dimensions: (1) Knowledge (epistemological), emphasizing the acquisition and application of knowledge for goodness and wisdom; (2) Faith (theological), fostering sincerity and spiritual awareness in the learning process; and (3) Morality (ethical-social), directing knowledge toward virtuous action and human civilization. These three dimensions form a holistic unity in nurturing insān kāmil—the complete human who is intellectually enlightened, spiritually mature, and morally upright. In the context of the Fifth Industrial Revolution and the digital era, Prophetic Education offers an alternative paradigm for Islamic education to address moral degradation and the secularization of knowledge through integrative curricula, adab-based pedagogy, and teacher exemplarity as the inheritors of prophetic values. Therefore, Prophetic Education in the hadiths of the Prophet ﷺ is not only theologically grounded but also contextually relevant and practically applicable as a foundational model for holistic, ethical, and civilization-oriented Islamic education.